2011
DOI: 10.1021/ef200051z
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Gasification Kinetics of Biomass Char Derived from High-Temperature Rapid Pyrolysis

Abstract: The char of three typical biomasses, rice straw char (RS char), chinar leaves char (CL char), and pine sawdust char (PS char), was prepared in a high-frequency furnace, which could efficiently reduce secondary reactions under rapid pyrolysis conditions at 800−1200 °C. The rapid pyrolysis char produced was isothermally gasified in a thermogravimetric analyzer (TGA) under a CO2 atmosphere. Effects of biomass type and pyrolysis temperature on intrinsic carbon structures and morphologic structures of char and furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
83
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(96 citation statements)
references
References 33 publications
12
83
0
1
Order By: Relevance
“…On the other hand, the existence of the char would be a potential problem for the recycling of further metal screening and refinement. The gasification behaviors of coal char and biomass char have already been widely studied (Zhang, Ashizawa, Kajitani & Miura, 2008;Yuan, Chen, Li & Wang, 2011;. For instance, Zhang et al (2008) have investigated the steam gasification of 14 kinds of biomass chars and found that the extended random pore model could predict the gasification rates of all 14 kinds of biomass chars very well.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, the existence of the char would be a potential problem for the recycling of further metal screening and refinement. The gasification behaviors of coal char and biomass char have already been widely studied (Zhang, Ashizawa, Kajitani & Miura, 2008;Yuan, Chen, Li & Wang, 2011;. For instance, Zhang et al (2008) have investigated the steam gasification of 14 kinds of biomass chars and found that the extended random pore model could predict the gasification rates of all 14 kinds of biomass chars very well.…”
Section: Introductionmentioning
confidence: 99%
“…studied the CO 2 gasification behaviors of various coal chars and concluded that the CO 2 gasification behaviors had a close relationship with their physicochemical Properties, especially with the CO 2 chemisorbed volumes of chars. With regard to biomass and coal chars, the intrinsic alkali (K and Na), alkaline (Ca and Mg) and transition (Fe) metal contents also play important roles on the char gasification rates (Zhang, et al 2008;Yuan et al, 2011;Lahijania, Zainala, & Mohamedb, 2012). In addition, the Si and Al metal contents generally exert severe inhibition effect on the gasification reaction (Zhang, et al, 2008;Zhang, et al, 2010;Yuan, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However the produced char was generally taken out after the char is cooled and then it is again heated up and gasified. Furthermore, in most of the biomass gasification experiments, the number of biomass species are limited (Yuan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%